2006
DOI: 10.1021/np0600447
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Secolignans from Peperomia dindygulensis

Abstract: Thirteen secolignans, including eight new ones (1-8), were isolated from the EtOAc extract of Peperomia dindygulensis. The structures were mainly elucidated by 1D and 2D NMR and MS experiments, the relative configurations were determined by NOE correlations, and the absolute configurations were established by the optical rotations and CD spectra. Cytotoxicity and MDR (multidrug resistance) reversal activity of the isolated compounds were examined. Compounds 6 and 7, peperomins B (10) and E (12), showed moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 12 publications
(30 reference statements)
1
29
0
4
Order By: Relevance
“…Recently, we have reported that several secolignans isolated from the extract of Peperomia dindygulensis inhibit cell-surface ICAM-1 expression induced by pro-inflammatory cytokines. 81 However, except for their anti-inflammatory activity, 81 multidrug resistance reversal activity 81 and anticancer activity, 81,82 the biological activities of peperomins are little understood. Peperomin E and 2,6-didehydropeperomin B (Figure 4) are structural analogs of peperomin A and peperomin B in which the a-methylene-g-lactone groups are replaced with a-methyl-g-lactone groups, respectively.…”
Section: Thiol-reactive Ikk Inhibitorsmentioning
confidence: 99%
“…Recently, we have reported that several secolignans isolated from the extract of Peperomia dindygulensis inhibit cell-surface ICAM-1 expression induced by pro-inflammatory cytokines. 81 However, except for their anti-inflammatory activity, 81 multidrug resistance reversal activity 81 and anticancer activity, 81,82 the biological activities of peperomins are little understood. Peperomin E and 2,6-didehydropeperomin B (Figure 4) are structural analogs of peperomin A and peperomin B in which the a-methylene-g-lactone groups are replaced with a-methyl-g-lactone groups, respectively.…”
Section: Thiol-reactive Ikk Inhibitorsmentioning
confidence: 99%
“…Among the few examples that have been reported are the isolation of an antitumor dibenzylbutyrolactone derivative [43,44], and tetrahydrofuran lignans [45]. Several tetrahydrofuran lignans have also been isolated from Piper solmsianum, and these exhibit potent in vitro trypanocidal activities against trypomastigote forms of Trypanosoma cruzi, the causative agent of Chagas disease [46].…”
Section: © 2007 Iupac Pure and Applied Chemistry 79 529-538mentioning
confidence: 99%
“…Some structurally related compounds from Peperomia, including prenylated phenolics [16] and polyketide-chromenes [17,18], have been reported. Additionally, compounds derived from the shikimate pathway are also well represented in Peperomia species and these include the secolignans, the peperomins, and the styrene dimers derived from phenylpropanoid in which the γ-carbon is absent [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Entre as espécies estudadas, podem ser citadas Peperomia proctorii (Seeram et al, 2000), Peperomia galiodes (Mahiou et al, 1995), Peperomia dindigulensis (Govindachari et al, 1998;Wu et al, 2006), Peperomia pellucida (Xu et al, 2006) e Peperomia villipetiola (Salazar et al, 2005).…”
Section: Um Exemplo De Espécie Popular E Mais Estudada Pertencente Aounclassified
“…As peperominas A (17) e E (18) encontram-se descritas na literatura, com registros de atividade antifágica frente a Spodoptera litura, Rhaphidopalpa foveicollis e Atractomorpha crenulata (Govindachari et al, 1998) e anti-tumoral (células VA-13 e HepG2) (Wu et al, 2006). Entretanto, não há nenhum relato sobre o potencial antifúngico destas substâncias.…”
Section: Dos Metabólitos Isolados Deunclassified